Austenitic stainless steel welding wire for liquid hydrogen storage tank and preparation method and application of austenitic stainless steel welding wire
By adopting the Fe-Cr-Ni-Mn-Mo-N alloy system and optimizing the smelting process, the content of Mo and N elements is controlled, and the welds are ensured to be a single-phase austenite structure, which solves the problem of poor low-temperature performance of austenite stainless steel welding materials in liquid hydrogen storage tank welding, and achieves high strength and high toughness weld performance.
Patent Information
- Application Number
- CN202510951094.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-10
- Publication Date
- 2025-08-29
AI Technical Summary
When welding liquid hydrogen storage tanks, the existing austenitic stainless steel welding materials have poor low temperature performance and are prone to brittle fracture. The oxide content in the weld is high, which affects the low temperature performance.
The Fe-Cr-Ni-Mn-Mo-N alloy system is adopted, combined with medium-frequency induction smelting, argon oxygen decarbonization and electroslag remelting remelting remelting processes, control the Mo and N elements contents, and use the MIG welding process to avoid oxide inclusions and ensure that the weld is a single-phase austenite structure.
The low-temperature strength, plasticity and toughness of the welds are improved, and meet the strict service requirements of liquid hydrogen storage tanks. The post-welded metal shows excellent tensile strength, yield strength and fracture toughness at -269℃.
Smart Images

Figure CN120551641A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of welding materials and their preparation, and particularly relates to an austenitic stainless steel welding wire for liquid hydrogen storage tanks, a preparation method and application thereof. Background Art
[0002] As a clean, low-carbon energy source, hydrogen is a crucial component of my country's future energy system. Cryogenic liquid hydrogen storage technology, with its advantages of high hydrogen storage density, high energy density, and excellent safety, has become a key development direction for hydrogen energy storage technology. With the increasing popularity of cryogenic technology, demand for liquid hydrogen is increasing across various industries. Liquid hydrogen is widely used in aerospace, transportation, and industry, such as as a power source for aircraft, rockets, automobiles, and ships, as well as in synthetic ammonia, coal chemical industry, metal smelting, and energy storage and power generation. Therefore, the storage of cryogenic liquid hydrogen has significant economic value. However, current liquid hydrogen storage technology is still in its infancy. Liquid hydrogen storage tanks are key equipment in the liquid hydrogen industry, used to store liquid hydrogen. Gaseous hydrogen is compressed and cooled to -253°C to liquefy it, and then stored in insulated vacuum tanks. Therefore, the manufacture of liquid hydrogen storage tanks is of great significance.
[0003] Liquid hydrogen storage tanks are cryogenic containers. Austenitic stainless steel generally does not become brittle at low temperatures and has a low cost, so it is often used as a structural material for cryogenic containers. However, austenitic stainless steel welded joints are weak parts of the structure and may suffer brittle fractures under low temperature conditions, leading to serious accidents. At present, austenitic stainless steel welding materials such as 308L and 316L are widely used in austenitic stainless steel welding, but there is a certain amount of ferrite in the weld structure, which is prone to severe brittleness in low temperature environments, deteriorating the low-temperature performance of the welded joints. Therefore, the development of austenitic stainless steel welding materials suitable for liquid hydrogen storage tanks to ensure the low-temperature performance of the welded joints has become a key challenge in liquid hydrogen storage technology.
[0004] Low-temperature environments place stringent demands on the low-temperature performance of welding materials and weld joints. Oxides in the weld can degrade the low-temperature performance of the weld metal. These oxides primarily originate from the smelting and welding processes, and the oxygen content of the weld metal reflects the presence of oxides in the weld metal. Conventional medium-frequency induction-smelted austenitic stainless steel wires, when welded using the MAG welding process, often have high oxygen content, resulting in poor low-temperature performance. Therefore, optimizing the smelting and welding processes to reduce the oxygen content in the weld and improve the low-temperature performance of austenitic stainless steel welds used in liquid hydrogen storage tanks is urgently needed. Summary of the Invention
[0005] In order to solve the problem of poor low-temperature performance of welds of existing austenitic stainless steel welding materials when welding liquid hydrogen storage tanks, the present invention provides an austenitic stainless steel welding wire for liquid hydrogen storage tanks, a preparation method and an application thereof.
[0006] To achieve the above object, the technical solution of the present invention is as follows: One of the objects of the present invention is to provide an austenitic stainless steel welding wire, the chemical composition of which, expressed in percentage by mass, is as follows: C≤0.02%, Si: 0.4-1.5%, Mn: 5.0-7.5%, S≤0.020%, P≤0.030%, Cr: 16.0-22.0%, Ni: 15.0-18.0%, Mo: 2.0-5.0%, N: 0.05-0.2%, O≤0.01%, and the balance being Fe and unavoidable impurities.
[0007] It is further defined that the chemical composition of the welding wire is expressed in mass percentage: C≤0.02%, Si: 0.4~1.0%, Mn: 5.0~7.5%, S≤0.020%, P≤0.030%, Cr: 16.0~22.0%, Ni: 15.0~18.0%, Mo: 2.5~4.5%, N: 0.05~0.1%, O≤0.008%, and the balance is Fe and unavoidable impurities.
[0008] A second object of the present invention is to provide a method for preparing the above-mentioned austenitic stainless steel welding wire, which includes medium frequency induction smelting, argon oxygen decarburization refining, electroslag remelting refining, forging, rolling and drawing processes.
[0009] A third object of the present invention is to provide an application of the above-mentioned austenitic stainless steel welding wire, specifically, the welding wire is used for welding austenitic stainless steel liquid hydrogen storage tanks.
[0010] It is further defined that the welding wire is used for welding 304LN and 316LN austenitic stainless steel liquid hydrogen storage tanks.
[0011] It is further defined that welding shall be carried out using metal inert gas shielded welding.
[0012] Further definition, the parameters of the metal inert gas shielded welding are: the current type is DCEP, the welding current is 200~260A, the arc voltage is 24~32V, the shielding gas is pure Ar gas, the gas flow rate during welding is 15~20L / min, and the interlayer temperature is less than 150℃.
[0013] It is further specified that the deposited metal used for welding austenitic stainless steel liquid hydrogen storage tanks must have a tensile strength of ≥1200 MPa at -269°C, a yield strength of ≥1000 MPa, an elongation after fracture of ≥20%, an impact absorption energy of ≥100 J at -269°C, and a fracture toughness of ≥150 MPa·m at -269°C. 1 / 2 .
[0014] The present invention has the following beneficial effects: (1) The austenitic stainless steel welding wire provided by the present invention adopts the Fe-Cr-Ni-Mn-Mo-N alloy system, so that the deposited metal of the welding wire is a single-phase austenite structure, and its low-temperature embrittlement tendency is much lower than the deposited metal formed by conventional 300 series austenitic stainless steel welding wire.
[0015] (2) The present invention regulates the total content of Mo and N elements. Although a low total content of the two elements makes the deposited metal have better low-temperature toughness, it will reduce the strength of the deposited metal at low temperatures, while too high a total content will make the low-temperature toughness worse. Therefore, the present invention controls the content of the two elements within 2.05%≤Mo+N≤5.2%, which not only ensures that the deposited metal has high low-temperature strength, but also has excellent low-temperature impact and fracture toughness to meet the stringent service requirements of liquid hydrogen storage tanks.
[0016] (3) The present invention uses a process that combines medium-frequency induction smelting, AOD refining (argon oxygen decarburization refining) and electroslag remelting to effectively reduce the oxygen content in austenitic stainless steel welding wire. At the same time, the welding process is optimized, and the traditional MAG welding is adjusted to MIG welding. The shielding gas used does not contain oxygen, which further reduces the oxide inclusions in the deposited metal, obtains a low-oxygen deposited metal, and improves the low-temperature impact and fracture toughness of the deposited metal.
[0017] (4) The deposited metal of the austenitic stainless steel welding wire provided by the present invention has a tensile strength of ≥1200 MPa at -269°C, a yield strength of ≥1000 MPa, an elongation after fracture of ≥20%, an impact absorption energy of ≥100 J at -269°C, and a fracture toughness of ≥150 MPa·m at -269°C. 1 / 2 . BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 The metallographic structure of the MIG weld deposited metal obtained in Example 1; Figure 2 The metallographic structure of the MIG weld deposited metal obtained in Example 2; Figure 3 The metallographic structure of the MIG weld deposited metal obtained in Example 3; Figure 4 The metallographic structure of the MIG weld deposited metal obtained in Comparative Example 1; Figure 5 The metallographic structure of the MIG weld deposited metal obtained in Comparative Example 2; Figure 6 The metallographic structure of the MAG weld deposited metal obtained in Comparative Example 3; Figure 7 This is the metallographic structure of the MIG weld deposited metal obtained in Comparative Example 4. DETAILED DESCRIPTION
[0019] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0020] In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention may also be implemented in other ways different from those described herein. Those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0021] Secondly, the term "one embodiment" or "embodiment" herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in various places throughout this specification does not necessarily refer to the same embodiment, nor does it constitute a separate or selective embodiment that is mutually exclusive of other embodiments.
[0022] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods, and instruments used are conventional in the art and can be obtained commercially by those skilled in the art unless otherwise specified.
[0023] Example 1 This embodiment provides an austenitic stainless steel welding wire for a liquid hydrogen storage tank, the chemical composition of which is expressed in mass percentage as follows: C: 0.011%, Si: 0.55%, Mn: 5.34%, S: 0.0041%, P: 0.008%, Cr: 18.6%, Ni: 16.8%, Mo: 3.82%, N: 0.06%, O: 0.0054%, and the balance is Fe and unavoidable impurities, as shown in Table 1 for details.
[0024] The austenitic stainless steel welding wire is prepared through the process of medium frequency induction smelting → AOD refining → electroslag remelting refining → forging → rolling → drawing to produce a welding wire with a specification of Φ1.2mm.
[0025] The austenitic stainless steel wire was used to prepare MIG weld deposits. The welding current type was DCEP (direct current reverse polarity), the welding current was 220A, the arc voltage was 28V, the shielding gas was Ar, the gas flow rate during welding was 20L / min, and the interpass temperature was less than 150°C. The tensile properties, impact properties, and fracture properties of the MIG weld deposits were tested at -269°C, and the metallographic structure was observed. The results are shown in Table 2. The metallographic structure of the MIG weld deposits is shown in Table 2. Figure 1 As shown, the oxygen content of the deposited metal is 0.0077%.
[0026] Example 2 The difference between this embodiment and embodiment 1 is that the chemical composition of the austenitic stainless steel welding wire is expressed in percentage by mass as follows: C: 0.0087%, Si: 0.62%, Mn: 6.14%, S: 0.0049%, P: 0.0062%, Cr: 19.4%, Ni: 17.1%, Mo: 3.05%, N: 0.08%, O: 0.0067%, and the balance is Fe and unavoidable impurities, as shown in Table 1. The remaining operating steps and parameter settings are the same as those in embodiment 1. The tensile properties, impact properties, and fracture properties of the MIG weld deposited metal were tested at -269°C, and the metallographic structure was observed. The results are shown in Table 2. The metallographic structure of the MIG weld deposited metal is shown in Table 2. Figure 2 As shown in Figure 2, the oxygen content of the deposited metal is 0.0082%.
[0027] Example 3 The difference between this embodiment and embodiment 1 is that the chemical composition of the austenitic stainless steel welding wire is expressed in percentage by mass as follows: C: 0.0072%, Si: 0.75%, Mn: 6.21%, S: 0.0074%, P: 0.0084%, Cr: 18.5%, Ni: 16.2%, Mo: 2.58%, N: 0.08%, O: 0.0072%, and the balance is Fe and unavoidable impurities, as shown in Table 1. The remaining operating steps and parameter settings are the same as those in embodiment 1. The tensile properties, impact properties, and fracture properties of the MIG weld deposited metal were tested at -269°C, and the metallographic structure was observed. The results are shown in Table 2. The metallographic structure of the MIG weld deposited metal is shown in Table 2. Figure 3 As shown in Figure 2, the oxygen content of the deposited metal is 0.0074%.
[0028] Comparative Example 1 The difference between this comparative example and Example 1 is that the welding wire is prepared by medium frequency induction smelting → forging → rolling → drawing process. The chemical composition of the welding wire is expressed in percentage by mass as follows: C: 0.014%, Si: 0.59%, Mn: 6.07%, S: 0.0052%, P: 0.016%, Cr: 19.2%, Ni: 17.5%, Mo: 3.74%, N: 0.06%, O: 0.018%, and the remainder is Fe and unavoidable impurities, see Table 1 for details. The remaining operating steps and parameter settings are the same as those in Example 1. The tensile properties, impact properties, fracture properties and metallographic structure of the MIG welding deposited metal were tested at -269°C, and the results are shown in Table 2. The metallographic structure of the MIG welding deposited metal is as shown in Table 2. Figure 4 As shown in Figure 2, the oxygen content of the deposited metal is 0.022%.
[0029] Comparative Example 2 The difference between this comparative example and Example 1 is that the chemical composition of the austenitic stainless steel welding wire is expressed in percentage by mass as follows: C: 0.0089%, Si: 0.22%, Mn: 5.72%, S: 0.008%, P: 0.0089%, Cr: 18.9%, Ni: 16.7%, Mo: 3.97%, N: 0.06%, O: 0.0066%, and the balance is Fe and unavoidable impurities, as shown in Table 1. The remaining operating steps and parameter settings are the same as those in Example 1. The tensile properties, impact properties, and fracture properties of the MIG weld deposited metal were tested at -269°C, and the metallographic structure was observed. The results are shown in Table 2. The metallographic structure of the MIG weld deposited metal is shown in Table 2. Figure 5 As shown in Figure 2, the oxygen content of the deposited metal is 0.064%.
[0030] Comparative Example 3 The difference between this comparative example and Example 1 is that the chemical composition of the austenitic stainless steel welding wire is expressed in percentage by mass as follows: C: 0.012%, Si: 0.52%, Mn: 5.47%, S: 0.0067%, P: 0.0083%, Cr: 18.8%, Ni: 17.1%, Mo: 3.83%, N: 0.06%, O: 0.0061%, and the balance is Fe and unavoidable impurities, see Table 1 for details. MAG welding deposited metal was prepared using the above-mentioned austenitic stainless steel welding wire. The shielding gas during the welding process was 97% Ar + 3% CO2. The remaining operating steps and parameter settings were the same as in Example 1. The tensile properties, impact properties, fracture properties and metallographic structure of the MAG welding deposited metal were tested at -269°C. The results are shown in Table 2. The metallographic structure of the MAG welding deposited metal is shown in Table 2. Figure 6 As shown in Figure 2, the oxygen content of the MAG weld deposit is 0.038%.
[0031] Comparative Example 4 The difference between this comparative example and Example 1 is that the chemical composition of the austenitic stainless steel welding wire is expressed in percentage by mass as follows: C: 0.0092%, Si: 0.58%, Mn: 5.52%, S: 0.0076%, P: 0.0083%, Cr: 18.7%, Ni: 16.9%, Mo: 5.23%, N: 0.25%, O: 0.0052%, and the balance is Fe and unavoidable impurities, as shown in Table 1. The remaining operating steps and parameter settings are the same as those in Example 1. The tensile properties, impact properties, and fracture properties of the MIG weld deposit were tested at -269°C, and the metallographic structure was observed. The results are shown in Table 2. The metallographic structure of the MIG weld deposit is shown in Table 2. Figure 7 As shown in Figure 2, the oxygen content of the deposited metal is 0.0059%.
[0032] Table 1 Chemical composition of welding wires of embodiment and comparative example (mass percentage, %)
[0033] Table 2 Test results of mechanical properties of deposited metal
[0034] It can be seen from Tables 1 to 2 above that the plasticity and toughness of the deposited metal of the austenitic stainless steel welding wires of Comparative Examples 1 to 4 are poor, the ability to resist crack propagation at low temperatures is poor, and there is a certain tendency to embrittlement. The deoxidation effect of the medium frequency induction smelting process of Comparative Example 1 is not as good as the deoxidation effect of medium frequency induction smelting + AOD refining + electroslag remelting refining, resulting in a high oxygen content in the deposited metal, which is not conducive to the plasticity and toughness of the deposited metal. The Si content of the austenitic stainless steel welding wire of Comparative Example 2 is too low, resulting in an unstable welding process, serious oxygenation of the deposited metal, and deterioration of the plasticity and toughness of the deposited metal. Comparative Example 3 uses MAG welding for welding. Since the shielding gas contains CO2, oxygen will be transferred to the molten pool during the welding process, causing the oxygen content of the deposited metal to increase, so the plasticity and toughness of the deposited metal are low. The Mo and N content of the austenitic stainless steel welding wire in comparative example 4 is too high, and the sum of the two is 5.48%, which is not within the range of 2.05%≤Mo+N≤5.2%. The strengthening effect is too large, so the low-temperature strength of the deposited metal is high, but the plasticity and toughness at low temperatures cannot meet the welding requirements of low-temperature liquid hydrogen storage tanks. The austenitic stainless steel welding wire provided by the present invention controls the Si content to be above 0.4%, the welding process is stable, and the deposited metal has no obvious oxygenation. At the same time, the MIG welding process is adopted to avoid the oxidation of the deposited metal by the active shielding gas. After welding, the deposited metal is a single-phase austenite structure, which avoids the embrittlement of ferrite at low temperatures and has excellent low-temperature strength, plasticity and toughness. The tensile strength at -269°C is ≥1200MPa, the yield strength is ≥1000MPa, the elongation after fracture is ≥20%, the impact absorption energy at -269°C is ≥100J, and the fracture toughness at -269°C is ≥150MPa·m 1 / 2 In summary, the austenitic stainless steel welding wire MIG welding provided by the present invention has excellent comprehensive mechanical properties and is suitable for welding low-temperature liquid hydrogen storage tanks.
[0035] Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Anyone familiar with this technology can make various changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention should be based on the definition of the claims.
Claims
1. An austenitic stainless steel welding wire for liquid hydrogen storage tanks, characterized in that: The chemical composition of the welding wire is expressed in mass percentage: C≤0.02%, Si: 0.4~1.5%, Mn: 5.0~7.5%, S≤0.020%, P≤0.030%, Cr: 16.0~22.0%, Ni: 15.0~18.0%, Mo: 2.0~5.0%, N: 0.05~0.2%, O≤0.01%, and the balance is Fe and inevitable impurities.
2. The welding wire according to claim 1, characterized in that The chemical composition of the welding wire is expressed in mass percentage: C≤0.02%, Si: 0.4~1.0%, Mn: 5.0~7.5%, S≤0.020%, P≤0.030%, Cr: 16.0~22.0%, Ni: 15.0~18.0%, Mo: 2.5~4.5%, N: 0.05~0.1%, O≤0.008%, the balance is Fe and unavoidable impurities.
3. A method for preparing the welding wire according to claim 1 or 2, characterized in that: The method includes medium frequency induction smelting, argon oxygen decarburization refining, electroslag remelting refining, forging, rolling and drawing processes.
4. Use of the welding wire according to claim 1 or 2, characterized in that: This welding wire is used for welding austenitic stainless steel liquid hydrogen storage tanks.
5. The use according to claim 4, characterized in that This welding wire is used for welding 304LN and 316LN austenitic stainless steel liquid hydrogen storage tanks.
6. A welding process used in the application according to claim 4 or 5, characterized in that: The welding is carried out using metal inert gas shielded welding.
7. The welding process according to claim 6, characterized in that Melting inert gas shielded welding parameters: current type is DCEP, welding current is 200~260A, arc voltage is 24~32V, shielding gas is pure Ar gas, gas flow rate during welding is 15~20L / min, and interlayer temperature is less than 150℃.
8. A deposited metal obtained by the application of any one of claims 4 to 7, characterized in that: The deposited metal has a tensile strength of ≥1200 MPa at -269°C, a yield strength of ≥1000 MPa, an elongation after fracture of ≥20%, an impact absorption energy of ≥100 J at -269°C, and a fracture toughness of ≥150 MPa·m at -269°C. 1 / 2 .
Citation Information
Cited By
Welding method of austenitic stainless steel for low-temperature storage tank
CN121131936A
Gas metal arc welding solid welding wire for extremely-low-temperature high-manganese high-aluminum austenitic steel as well as preparation method and application of gas metal arc welding solid welding wire
CN122033511A
